Why the Growth of Qanun Jinayah in Aceh was Slowly? An Analysis Using Structural Functionalism Theory - Roslaili, Yuni; Suparwany, Suparwany; Ahmad Nadzri, Amirulhakim Bin (Al-Risalah, 2021)
The growth of Qanun Jinayah in Aceh is running stagnantly, although the implementation of Islamic Sharia has been implementing for seventeen years. The local government ratified only five qanun Jinayah.Â  In fact, within that time, Aceh Government had imposed 177 qanuns and the crime rate in the region is increasing. Based on the case, this article aims to discuss recent progress of Jinayah law in Aceh and the challenges it faces. Then, using structural-functionalism theory discuss how coordination among sharia institutions worked as part of totality implementation of Islamic law in Aceh. By using qualitative and descriptive-interpretative methods, to examine interpretations and experiences of the subjects, in this case the sharia institutions, including Islamic Sharia Office, the Ulama Consultative Council, Sharia Court, and Sharia police, during their effort to implement Islamic Sharia. And finally, draw conclusion that the growth and development of Jinayah law in Aceh was prolonged because of weak coordination function among the sharia institutions. Therefore, it required a systematic approach based on structural-functionalism theory to encourage coordination between the sharia institutions in supporting the kaffah implementation of Islamic law in Aceh, including its Jinayah law.